Congenital Cervical Vertebral Malformation in Lambs - Fonteque, Joandes Henrique; de Souza, Anderson Fernando; Muller, Thiago Rinaldi; Gonçalves, Ronaldo Paiva Moreno; Granella, Milena Carol Sbrussi; Mendes, Rubens Peres; Schade, Jackson (Acta Scientiae Veterinariae, 2018)
Background: The occurrence of congenital defects in the sheep is estimated to be between 0.2% and 2%. For congenital anatomical alterations, diagnostic imaging allows objective understanding and evaluation, and is a great aid in the formulation of clinical decisions. Most of these anomalies are diagnosed by radiography; but computed tomography (CT) can provide important additional information. In the current literature there are no descriptions of the use of radiography and CT for a more detailed evaluation of the anatomical structures in cases of congenital cervical malformations in lambs. The objective of this study is to report the clinical, radiographic and tomographic findings in two cases of congenital cervical vertebral malformation in lambs. Cases: Two lambs with cervical morphological alterations since birth were attended. A 4-month-old mixed-breed lamb, weighing 11 kg, with lateroventrocaudal deviation of the neck was observed to the right side, not yielding to the attempt of repositioning. The owner reported that these changes were identified since birth, leading to difficulties in suckling colostrum, necessitating artificial feeding. With the growth of the animal, worsening of the cervical deviation resulted in the impossibility of grazing. The radiographs of the cervical spine identified marked scoliosis, and the axis presented small dimensions and morphological changes with a slight loss of atlantoaxial articular relationship. Spondylopathies were detected along the cervical spine. Other lamb of the Lacaune breed, weighing 4.2 kg, was presented shortly after birth with changes in the shape and posture of the neck, difficult locomotion and in sternal decubitus. The owner reported that the lamb came from a twin eutocic birth, with the other lamb being apparently normal. The animal was unable to ingest the colostrum, in which the sheep was milked and colostrum was offered through a bottle. Lateroventrocaudal deviation of the neck to the left side did not yield to the repositioning attempt, the mandible also presented left lateral deviation. The radiographs of the cervical spine showed morphological changes in atlas, and it was not possible to delimit its wings; it was also observed that the dorsal blade was parallel to the spinal process of the axis. The presence of a hypoattenuating linear left lateral image of the dorsal arch and a right ventro-lateral aspect of the atlas body was identified with slightly irregular and sclerotic margins, suggesting fracture lines. The body of the axis presented a conformational alteration with irregular contours and a large free fragment in the cranial aspect, suggestive of being the odontoid process, with rotation and deviation to the left in relation to the atlas. The right lateral cranial articular process of the third cervical vertebra (C3) presented a conformational change and important lateral rotation of the axis. Mild stenosis of the medullary canal was observed in the segment adjacent to C3. The euthanasia was recommended. Discussion: Congenital cervical malformations in sheep are rare in the literature and may lead to serious decrease in the quality of life of the animals. Computed tomography was superior to radiography in morphological evaluation in cases of congenital cervical malformations in sheep. However, both diagnostic methods were important to establish the best clinical behavior. The etiology of most congenital malformations is unknown, simply because of the complexity of the mechanisms that lead to the formation of an abnormality. The isolated episodes of this anomaly, in the herd without previous alterations, suggest a non-infectious cause, probably similar among the cases, but not established. The information presented can be used to validate clinical reasoning in future cases similar to those described, where imaging features are not available. Keywords: anomalies, fetus, radiography, computed tomography.